The Interplay Between Innate Lymphoid Cells and the Tumor Microenvironment - Ducimetière, Laura; Vermeer, Marijne; Tugues, Sonia (Frontiers in Immunology, 2019)
The multifaceted roles of Innate Lymphoid Cells (ILC) have been widely interrogated in tumor immunity. Whereas Natural Killer (NK) cells possess undisputable tumor-suppressive properties across multiple types of cancer, the other ILC family members can either promote or inhibit tumor growth depending on the environmental conditions. The differential effects of ILCs on tumor outcome have been attributed to the high degree of heterogeneity and plasticity within the ILC family members. However, it is now becoming clear that ILCs responses are shaped by their dynamic crosstalk with the different components of the tumor microenvironment (TME). In this review, we will give insights into the molecular and cellular players of the ILCs-TME interactions and we will discuss how we can use this knowledge to successfully harness the activity of ILCs for anticancer therapies.